Desert Indian Woman : Stories and Dreams - Manuel, Frances Sallie, 1912- (Book collections on Project MUSE., 2001)
Basket weaver, storyteller, and tribal elder, Frances Manuel is a living preserver of Tohono O'odham culture. Speaking to anthropologist Deborah Neff, who has known her for over twenty years, she tells of O'odham culture and society and of the fortunes and misfortunes of Native Americans in the southwestern borderlands over the past century.